Paul Feyerabend and Marxism - Guo, Yuanlin; Yan, Chubi (Filozoficzne Aspekty Genezy, 2024)
This article discusses the relationship between Paul Feyerabend and Marxism. Feyerabend mentioned, referenced, quoted, discussed or commented on the following Marxists, communists or leftists in his writings: Marx, Engels, Lenin, Stalin, MAO, Fidel Castro, Karl Kautsky, Eduard Bernstein, Rosa Luxemburg, Leon Trotsky, Bertolt Brecht, Hanns Eisler, Walter Hollitscher, Georg Lukacs, Ernst Bloch, Herbert Marcuse, Theodor Adorno, Jürgen Habermas, Joseph Needham, Jean-Paul Sartre, Walter Benjamin, Louis Althusser, Daniel Cohn-Benit and Robin Blackburn. On numerous occasions he discussed and commented on Dadaism, Marxism, communism, anarchism, liberalism, dialectical materialism, reductive materialism and, especially, eliminative materialism. He originated a Dadaistic philosophy, and in particular a Dadaistic epistemology. He did not convert to dialectical materialism; nevertheless, Dadaism seems highly relevant to Marxism and communism. As a Dadaist in philosophy he could well have been a Marxist, a non-Marxist, or an anti-Marxist.